Relationship between flexible working arrangement and employee turnover intention in China : a study of the effects of organizational justice, commitment and demographics - Liu, Tieying (2008)
The key factors to succeed in any market not only include the knowledge of consumers' behavior, and product market situation, but also the ability to manage employees effectively. In today's business environment, companies place a high value on attending to the needs of their employees whom they portray as their most valuable intangible assets.